2013
DOI: 10.1007/s00464-013-2865-z
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic safety of stent as bridge to surgery compared to emergency radical surgery for left-sided colorectal cancer obstruction

Abstract: For left-sided colorectal cancer obstruction, stent insertion followed by surgery showed short-term advantages and similar oncologic outcomes compared to surgery without preoperative intervention. Stent insertion as a bridge to surgery is a safe and feasible treatment option for patients with colorectal cancer obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 32 publications
2
16
1
2
Order By: Relevance
“…The authors acknowledge that the present study was limited by the retrospective non-randomized design, small numbers and difference in baseline tumour stage between groups. Still, these outcomes are in line with the results of a recent oriental study 15 . French 14 and South Korean 12 studies, however, showed worse 5-year overall survival with SEMS insertion.…”
Section: Discussionsupporting
confidence: 90%
“…The authors acknowledge that the present study was limited by the retrospective non-randomized design, small numbers and difference in baseline tumour stage between groups. Still, these outcomes are in line with the results of a recent oriental study 15 . French 14 and South Korean 12 studies, however, showed worse 5-year overall survival with SEMS insertion.…”
Section: Discussionsupporting
confidence: 90%
“…Oncologic outcomes between elective surgery following colonic stenting and emergency surgery are controversial. Some studies reported comparable oncologic outcomes of elective surgery after colonic stenting to emergency surgery [12][13][14]. In contrast to our findings, worse oncologic outcomes of colonic stenting were published [15,16].…”
Section: Fig 2 (A)contrasting
confidence: 87%
“…The group from St Vincent's University Hospital in Dublin showed similar overall and cancer‐specific survival in 49 patients. This has been echoed by others, but there have also been reports of a negative impact on cancer outcomes. One retrospective study used a propensity score to adjust for allocation bias in 48 patients who received a bridging stent and 39 who underwent emergency surgery.…”
Section: Discussionmentioning
confidence: 79%